Konflik Hukum Dalam Proyek Konstruksi Antara Wanprestasi Dan Perbuatan Melawan Hukum - Pratama Hinelo, Ananta; Cherawaty Thalib, Mutia; T. Mandjo, Julius (YUDHISTIRA : Jurnal Yurisprudensi, Hukum dan Peradilan, 2025)
Construction contract conflicts often arise due to default and unlawful acts that cause losses to the parties, so a legal analysis is needed to strengthen legal certainty and justice. This study examines the issue of breach of contract and unlawful acts in construction contracts through a legal analysis of two court decisions: Decision Number 433/Pdt.G/2021/PN Jkt.Pst and Decision Number 46/Pdt.G/2018/PN Bgr. These two cases illustrate two forms of legal violations in the implementation of construction contracts that result in losses for both the service provider and the service user. In the first case, the breach occurred due to the debtor's negligence in fulfilling the agreed-upon performance, resulting in a claim for compensation. In the second case, the violation of the initial agreement led to delays in work completion, which then resulted in the provider being blacklisted and the contract termination by the service user. This study highlights the importance of contractual understanding, strengthening construction regulations, and effective dispute resolution mechanisms in preventing similar conflicts in the future. This study also emphasizes that work delays are not always the fault of the service provider but can be caused by changes on the part of the service user without an official extension. Therefore, efforts to improve the construction contractual system need to be strengthened to ensure legal certainty, justice, and efficiency in the implementation of construction projects in Indonesia.